2018
DOI: 10.1186/s13034-018-0222-7
|View full text |Cite
|
Sign up to set email alerts
|

Supervision trajectories of male juvenile offenders: growth mixture modeling on SAVRY risk assessments

Abstract: Background: Structured risk/need assessment tools are increasingly used to orientate risk reduction strategies with juvenile offenders. The assumption is that the risk/need items on these tools are sufficiently sensitive to measure changes in the individual, family and/or contextual characteristics of juvenile offenders. However, there is very little research demonstrating the capacity of these tools to measure changes in juvenile offenders. Congruent with the developmental and life-course criminology theories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…There was a small group of youth probationers who had an increase in risk and needs after the probation orders (i.e., Escalators). This comprised about 4.1% of the sample, which corresponded well with the findings from Hilterman and colleagues (2018) who found that 4% of their youth offender sample was rapid escalators. A closer analysis showed that a longer probation order may lead to a higher risk of being Escalators.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…There was a small group of youth probationers who had an increase in risk and needs after the probation orders (i.e., Escalators). This comprised about 4.1% of the sample, which corresponded well with the findings from Hilterman and colleagues (2018) who found that 4% of their youth offender sample was rapid escalators. A closer analysis showed that a longer probation order may lead to a higher risk of being Escalators.…”
Section: Discussionsupporting
confidence: 86%
“…This finding is also similar to the study on parolees in the United States by Hochstetler and colleagues (2016); they found that about 33% were in the Consistently High-Risk group. In another study on male youth offenders, Hilterman and colleagues (2018) found that 23% of their sample was high persistors. However, it is unclear whether the risk levels are comparable among these studies, although these groups referred to youth with the highest risk/needs in each respective setting.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The Structured Assessment of Violence Risk in Youth (SAVRY) (Borum et al, 2002), a risk assessment instrument which has been developed to determine violence risk, was used. While the SAVRY has been developed for use in adolescents, several studies support the use of the SAVRY in offenders up to 25 years old (Hilterman et al, 2018;Kleeven et al, 2020;Vincent et al, 2019). The SAVRY is composed of 24 risk factors in three risk domains (historical scale, social/contextual scale, and individual/clinical scale), and a protective factor domain including six protective factors (for an overview of the SAVRY items see Table 1).…”
Section: Savrymentioning
confidence: 99%
“…In the second paper Ed Hilterman et al [10] present a longitudinal study on 5205 male juvenile offenders from the Catalan juvenile justice system. These youths received multiple SAVRY risk/need assessments over time.…”
mentioning
confidence: 99%